Cytokine Concentrations in Aqueous Humor of Eyes With Circumscribed Choroidal Hemangioma - Liu, Kailin; Guo, Lili; Cheng, Yong; Liang, Jianhong (Frontiers in Endocrinology, 2022)
Purpose: Anti-vascular endothelial growth factor (anti-VEGF) treatment are now widely used in patients with circumscribed choroidal hemangioma (CCH), however the concentrations of VEGF and other cytokines in CCH patients have not been known before. The study was conducted to compare various cytokine concentrations in the aqueous humor of eyes with CCH and control. Methods: A total of 16 eyes of 16 patients with CCH, and 15 eyes of 15 patients with cataract as the control group were examined. Aqueous humor samples were assessed for 30 angiogenic and inflammatory cytokines by Luminex bead-based multiplex array. Results: Significantly, compared with control group, higher concentrations of VEGF-A and IP-10 were found in the CCH patients (P = 0.002 and P < 0.001). Conclusions: VEGF-A and IP-10 might be involved with the angiogenic and antiangiogenic process in CCH patients, which provides new insight into the pathophysiology of CCH and could be potential targets for treatment.